Poziom A :
[tex]a] \ 1\frac{3}{5}-\frac{1}{2}=1\frac{6}{10}-\frac{5}{10}=1\frac{1}{10}\\\\b] \ 3\frac{5}{6}-1\frac{1}{4}=3\frac{10}{12}-1\frac{3}{12}=2\frac{7}{12}[/tex]
Poziom B :
[tex]a] \ 4\frac{1}{5}-1\frac{3}{5}=3\frac{6}{5}-1\frac{3}{5}=2\frac{3}{5}\\\\b] \ 12\frac{1}{8}-8\frac{5}{8}=11\frac{9}{8}-8\frac{5}{8}=3\frac{4}{8}=3\frac{1}{2}[/tex]
Poziom C :
[tex]a] \ 2\frac{1}{5}-1\frac{1}{2}=2\frac{2}{10}-1\frac{5}{10}=1\frac{12}{10}-1\frac{5}{10}=\frac{7}{10}\\\\b] \ 5\frac{3}{8}-2\frac{5}{6}=5\frac{9}{24}-2\frac{20}{24}=4\frac{33}{24}-2\frac{20}{24}=2\frac{13}{24}[/tex]